2007
DOI: 10.1002/pds.1497
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pioglitazone and rosiglitazone for hospitalization for acute myocardial infarction in type 2 diabetes

Abstract: Background Recent studies have raised concerns about potential increased cardiovascular (CV) risk in type 2 diabetes patients treated with some peroxisome proliferator-activated receptor gamma (PPAR-gamma) agonists. Objective To ascertain the risk of hospitalization for acute myocardial infarction (AMI) in type 2 diabetes patients treated with pioglitazone relative to rosiglitazone. Methodology Using data covering 2003-2006 from a large health care insurer in the US, a retrospective cohort study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
3

Year Published

2007
2007
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 22 publications
(25 reference statements)
2
41
3
Order By: Relevance
“…16 However, if rosiglitazone increases the risk of myocardial infarction, this may represent a neutral rather than protective effect of pioglitazone.…”
Section: Pioglitazone -Paradoxically Cardioprotective?mentioning
confidence: 99%
“…16 However, if rosiglitazone increases the risk of myocardial infarction, this may represent a neutral rather than protective effect of pioglitazone.…”
Section: Pioglitazone -Paradoxically Cardioprotective?mentioning
confidence: 99%
“…The results of the RECORD (Rosiglitazone Evaluated for Cardiac Outcomes and Regulation of Glycaemia in Diabetes) interim analysis and other meta-analyses showed that the risk of MI was significantly increased with rosiglitazone [71][72][73][74] . At present, it is not clear if there are differences between the two glitazones and whether or not any such potential variability is clinically relevant [71][72][73][74] .…”
Section: Antihyperglycaemic Therapiesmentioning
confidence: 99%
“…Since their publication, which has been widely criticised methodologically, 5 several studies have tried to confirm or contradict their results. Shortly after June 2007, a large cohort study 6,7 showed no statistically significant difference in the risk of AMI associated with rosiglitazone compared with other therapies (metformin, sulphonylurea), while another large retrospective cohort study 8 showed a significant AMI relative risk reduction among pioglitazone users compared with rosiglitazone users. In September 2007, another meta-analysis 9 of randomised clinical trials confirmed an increased risk of myocardial infarction without an increased risk of cardiovascular mortality among rosiglitazone users, and in December 2007, a Canadian nested case-control study 10 also revealed a significant increased risk of CHF, AMI and death in TZD users compared with other oral hypoglycaemic agent combination therapies, but this appeared limited to rosiglitazone.…”
Section: Introductionmentioning
confidence: 99%